2018
DOI: 10.1002/nbm.3910
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperglycemia alters the neurochemical profile, dendritic arborization and gene expression in the developing rat hippocampus

Abstract: Hyperglycemia (blood glucose concentration >150 mg/dL) is common in extremely low gestational age newborns (ELGANs; birth at <28 week gestation). Hyperglycemia increases the risk of brain injury in the neonatal period. The long-term effects are not well understood. In adult rats, hyperglycemia alters hippocampal energy metabolism. The effects of hyperglycemia on the developing hippocampus were studied in rat pups. In Experiment 1, recurrent hyperglycemia of graded severity (moderate hyperglycemia (moderate-HG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…The hippocampus was chosen for its critical role in cognitive functions by regulating learning, memory encoding, memory consolidation, and spatial navigation. In addition, the hippocampus is known to be vulnerable to different adverse effects, such as stress, 43 neonatal iron deficiency, 44 hyperglycemia, 45 or exposure to drugs 46 . Twelve female and 12 male mice used in protocol I were divided equally into two groups (control and exposed to 16.4 T).…”
Section: Resultsmentioning
confidence: 99%
“…The hippocampus was chosen for its critical role in cognitive functions by regulating learning, memory encoding, memory consolidation, and spatial navigation. In addition, the hippocampus is known to be vulnerable to different adverse effects, such as stress, 43 neonatal iron deficiency, 44 hyperglycemia, 45 or exposure to drugs 46 . Twelve female and 12 male mice used in protocol I were divided equally into two groups (control and exposed to 16.4 T).…”
Section: Resultsmentioning
confidence: 99%
“…In experimental settings, it has been shown that mechanisms of cerebral injury related to hyperglycemia include microglial activation, neuronal and glial apoptosis; hyperglycemia seems particularly prone to involve the hippocampus and the frontal cortex [20, 21]. In diabetic children, hyperglycemia is considered to be more detrimental for the developing brain than hypoglycemia [22], and asymptomatic hyperglycemia is associated with acute slowing of brain activity on the electroencephalogram [23].…”
Section: Discussionmentioning
confidence: 99%
“…Lower NAAG and Glu/Gln ratio, along with lower lactate, indicate decreased neuronal activity in the formerly iron-deficient hippocampus. 104,105 However, in the setting of lower taurine, decreased lactate also could indicate decreased oxidative glucose metabolism. 78 Consistent with this, Glut1 gene and protein expression is decreased in the formerly iron-deficient hippocampus, suggesting decreased brain glucose uptake.…”
Section: Evidence For Persistently Impaired Energy Metabolism Due To mentioning
confidence: 99%